Early cretaceous multi-stage extension in the North Dabie complex in the eastern central China: insights from structural and geochronological data - Huang, Peng; Yan, Zhen; Xiao, Wenjiao; Sang, Miao; Mao, Qigui; Abuduxun, Nijiati (Frontiers in Earth Science, 2024)
 The North Dabie extensional complex formed under NW-SE oriented extensional/transtensional strain regime in the Early Cretaceous  Ca. 144~138 Ma NW-SE oriented coaxial dominated plastic flow penetrated the middle-lower crust of the Dabie lithosphere  140~130 Ma large-scale low-angle detachment processing zone localized the extensional strain by top-to-NW ductile shearing in the middle crust  Sub-magmatic flow actively ascended from the lower crust in the diapiric manner during ca. 137~125 Ma.